2004
DOI: 10.1002/jrs.1168
|View full text |Cite
|
Sign up to set email alerts
|

Remote Raman spectroscopy as a prospective tool for planetary surfaces

Abstract: This paper summarizes the content of four Technical Notes that were established within a study contracted by the European Space Agency concerning the possibility of applying Raman spectroscopy in the field of remote imaging. An overview of the scientific demands and Raman spectroscopy from the user's point of view is provided together with a few key aspects in the field of planetary research. Laboratory Raman experiments were used for establishing a basis for the subsequent extrapolation to remote Raman spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…[59] Raman spectroscopy is also being used for in situ measurements of glasses at high temperature and pressure and has the potential for remote use on planetary surfaces. [57,[60][61][62][63][64] Similarly, the strategy employed to define physical properties of natural multicomponent melts could be adopted in compositional subgroups of material relevant for in industrial processes where continuous monitoring of melt and glass properties during production is important. [65,66] Our calibration strategy demonstrates the possibility to directly compare and interchange Raman data from silicate glasses collected (a) with different spectrometers, (b) in different labs, and (c) under different conditions, and (d) it obviates the need for measurements of melt composition and, thus, can expedite estimations of melt viscosity in various natural environments and, as a consequence, of various natural processes (e.g., melting, assimilation, and mixing of magmas) also where individual melt compositions are not easily sampled or measured (e.g., mixed magmas) or where research questions demand very large datasets of melt composition and physical properties.…”
Section: Discussionmentioning
confidence: 99%
“…[59] Raman spectroscopy is also being used for in situ measurements of glasses at high temperature and pressure and has the potential for remote use on planetary surfaces. [57,[60][61][62][63][64] Similarly, the strategy employed to define physical properties of natural multicomponent melts could be adopted in compositional subgroups of material relevant for in industrial processes where continuous monitoring of melt and glass properties during production is important. [65,66] Our calibration strategy demonstrates the possibility to directly compare and interchange Raman data from silicate glasses collected (a) with different spectrometers, (b) in different labs, and (c) under different conditions, and (d) it obviates the need for measurements of melt composition and, thus, can expedite estimations of melt viscosity in various natural environments and, as a consequence, of various natural processes (e.g., melting, assimilation, and mixing of magmas) also where individual melt compositions are not easily sampled or measured (e.g., mixed magmas) or where research questions demand very large datasets of melt composition and physical properties.…”
Section: Discussionmentioning
confidence: 99%
“…ExoMars program). Indeed, in the last years, Raman spectroscopy has been recognized as a promising tool for in situ and/or remote investigation of organic and inorganic material of bodies in our solar system . In particular, it has been demonstrated that Raman spectroscopy can be used both in situ and in remote conditions up to 100 m [e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Remote Raman spectroscopy from orbiting instruments would be a new tool for the investigation of planets. Klein et al (2004) presented the results of various feasibility studies commissioned by the European Space Agency to apply a remote Raman measurement device 10-100 m away from the landing site on a planetary body or even from the orbiting instruments. Their studies revealed that remote Raman spectroscopy will be a demanding task.…”
Section: Instrumentmentioning
confidence: 99%